2014
DOI: 10.1002/lary.24735
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of esophagopharyngeal reflux by augmenting the upper esophageal sphincter pressure barrier

Abstract: Objectives/Hypothesis Incompetence of the upper esophageal sphincter (UES) is fundamental to the occurrence of esophagopharyngeal reflux (EPR), and development of supraesophageal manifestations of reflux disease (SERD). However, therapeutic approaches to SERD have not been directed to strengthening of the UES barrier function. Our aims were to demonstrate that EPR events can be experimentally induced in SERD patients and not in healthy controls, and ascertain if these events can be prevented by application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 33 publications
1
30
0
1
Order By: Relevance
“…The pathophysiologic mechanisms of supra-esophageal manifestations of reflux disease or LPR are still today poorly understood [20], but there is another unsolved question: can surgery worsen LPR? The aim of this article is just speculative; starting from other important investigations in the literature and from our personal experiences, we have developed three main hypotheses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathophysiologic mechanisms of supra-esophageal manifestations of reflux disease or LPR are still today poorly understood [20], but there is another unsolved question: can surgery worsen LPR? The aim of this article is just speculative; starting from other important investigations in the literature and from our personal experiences, we have developed three main hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the striated muscles of UES are the most important barriers against pharyngeal reflux of acid contents; the cricopharyngeal muscle is one of the principal components of the UES, placed in front of the cervical vertebrae and behind the cricoid cartilage, very close to the thyroid capsule [20].…”
Section: °Hypothesis: the Upper Esophageal Sphinctermentioning
confidence: 99%
“…This question was addressed in a recent physiologic study by Shaker et al in 14 patients with extraesophageal symptoms and 12 healthy volunteers. 6 The authors reported that slow esophageal liquid infusion resulted in UES incompetence with subsequent laryngeal reflux events. However, reflux events were significantly reduced by application of a sustained predetermined externally applied cricoid pressure between 20-30 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 The Upper Esophageal Sphincter (UES) Assist Device is a novel medical device designed to prevent the reflux of gastric contents into the laryngopharynx. 6 It is a non-pharmacologic non-surgical medical device worn while sleeping and applies a standardized external pressure to the cricoid cartilage in order to decrease retrograde reflux of gastroduodenal contents ( Figure 1). Physiologic studies with this device have shown that application of 20-30 mmHg cricoid pressure by an external UES Assist Device, significantly increases the UES intraluminal pressure and prevents pharyngeal reflux induced by esophageal slow liquid infusion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation